Synthesis of Three‐Dimensional (Di)Azatricyclododecene Scaffold and Its Application to Peptidomimetics. Issue 46 (30th June 2021) - Umedera, Kohei; Morita, Taiki; Yoshimori, Atsushi; Yamada, Kentaro; Katoh, Akira; Kouji, Hiroyuki; Nakamura, Hiroyuki
Abstract: A novel sp 3 carbon‐rich tricyclic 3D scaffold‐based peptide mimetic compound library was constructed to target protein‐protein interactions. Tricyclic framework 7 was synthesized from 9‐azabicyclo[3, 3, 1]nonan‐3‐one (11) via a gold(I)‐catalyzed Conia‐ene reaction. The electron‐donating group on the pendant alkyne of cyclization precursor 12 b –e was the key to forming 6‐ endo ‐ dig cyclized product 7 with complete regioselectivity. Using the synthetic strategy for regioselective construction of bridged tricyclic framework 7, a diazatricyclododecene 3D‐scaffold 8 a, which enables the introduction of substituents into the scaffold to mimic amino acid side chains, was designed and synthesized. The peptide mimetics 21 a –u were synthesized via step‐by‐step installation of three substituents on diazatricyclododecene scaffold 8 a . Compounds 21 a –h were synthesized as α‐helix peptide mimics of hydrophobic ZZxxZ and ZxxZZ sequences (Z=Leu or Phe) and subjected to cell‐based assays: antiproliferative activity, HIF‐1 transcriptional activity which is considered to affect cancer malignancy, and antiviral activity against rabies virus. Compound 21 a showed the strongest inhibitory activity of HIF‐1 transcriptional activity (IC50 =4.1±0.8 μM), whereas compounds 21 a –g showed antiviral activity with IC50 values of 4.2–12.4 μM, suggesting that the 3D‐scaffold 8 a has potential as a versatile peptide mimic skeleton. Abstract : Three‐dimensional (3D) scaffolds have the potential to provide unique bioactivity, which cannot be achieved by conventional flat aromatic ring‐based compounds. (Di)Azatricyclododecene scaffold with a bridged tricyclic system was developed and applied to design peptidomimetics with a 3D scaffold. The designed peptidomimetics showed inhibition of HIF transcription activity and antiviral activity toward rabies virus, both of which α‐helix peptide mediated interaction play a pivotal role.